Economic implications of alternative disclosure rules for research and development costs* - HUGHES, JOHN S.; KAO, JENNIFER L. (Contemporary Accounting Research, 1991)
Abstract. This paper considers the effects of different rules regarding research and development (R&D) costs on competition in oligopolistic industries. It is shown that the consequences of those regimes on equilibrium levels of R&D spending depend on the impact of R&D on marginal costs and the risk attitudes of firm managers. Further results speak to the self‐selection of disclosure policies and the effects of those policies on social welfare. Generally speaking, the results are useful in forming predictions concerning the economic consequences of Statement of Financial Accounting Standards No. 2 and in explaining the information exchange activities of trade associations in high‐technology R&D industries. Résumé. Les auteurs analysent les conséquences de différentes règles relatives à la présentation de renseignements relatifs aux coûts de la recherche et du développement sur la concurrence dans les secteurs d'activité oligopolistiques. Ils établissent que les conséquences de la structure oligopolistique sur les niveaux d'équilibre des dépenses de recherche et de développement dépendent de l'incidence de ces activités sur les coûts marginaux et de l'attitude des cadres à l'égard du risque. Les auteurs tirent en outre des conclusions quant à l'autosélection de politiques relatives à la présentation de renseignements et aux conséquences de ces politiques sur l'intérêt de la société. Dans l'ensemble, les résultats de l'étude peuvent servir à l'élaboration de prédictions relatives aux conséquences économiques de la norme Statement of Financial Accounting Standards No. 2 et expliquer les activités d'échange d'information des associations commerciales dans les secteurs où la recherche et le développement technologiques sont importants.